Utilizing Heuristics and Metaheuristics for Solving the Set Covering Problem - Lourenço Sousa de Pinho (U.Porto Journal of Engineering, 2024)
A basic combinatorial optimization problem, the Set Covering Problem (SCP) finds extensive use in computer science, operations research, and logistics, among other domains. The SCP’s goal is to determine the smallest number of subsets, or sets, needed to cover every element precisely once given a finite set of items and a collection of subsets of these elements. Numerous practical uses for the SCP exist, such as crew scheduling, truck routing, and facility locating.